Investigation of spontaneous Brillouin scattering generation based on non-adiabatic microfibres - Zarei, A.; Jasim, Ali Abdulhadi; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2014)
Brillouin Stokes and anti-Stokes generation is successfully demonstrated in backward direction using a non-adiabatic microfibre as the gain medium. The Stokes light wavelength is up-shifted by 0.088 nm (10 GHz) from the BP wavelength as monitored by using an optical spectrum analyzer. The Brillouin scattering can also be enhanced by employing a microfibre based inline Mach–Zehnder interferometer (IMZI) as the gain medium due to its stronger multimode interference effect. It is shown that the microfibre geometry plays an important role in the spontaneous Brillouin scattering generation and gain bandwidth broadening due to its effect on irritation of the acoustic modes inside the microfibre.